2016
DOI: 10.1007/s10841-016-9869-7
|View full text |Cite
|
Sign up to set email alerts
|

Movement patterns of selected insect groups between natural forest, open land and rubber plantation in a tropical landscape (southern Yunnan, SW China)

Abstract: In many regions of tropical Asia, the expansion of rubber monoculture plantations is conducted by replacement of natural forest areas and strongly affects biodiversity and movement patterns of wild species, including insects. Against this background, we conducted a study on selected insect groups (longhorn beetles, bark beetles, wild bees and hoverflies) along transects between rainforest patches, open uncultivated land and rubber plantation habitats in a region of Xishuangbanna (southern Yunnan, China), with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Considering the convenience of management and transportation [55], rubber was mainly planted around urban areas, rural settlements, roads and rivers. Thus, the expansion of urban areas and the development of the road network enhanced the connectivity and aggregation of rubber (Table 5), while also leading to negative impacts on biodiversity, especially insects, such as beetles, spiders and wild bees [56,57]. In 1991, the Regulations on Lancang River Basin Protection in Xishuangbanna was passed for the purpose of the protection and rational exploitation of Lancang River Basin.…”
Section: Threats Of Rubber Plantationsmentioning
confidence: 99%
“…Considering the convenience of management and transportation [55], rubber was mainly planted around urban areas, rural settlements, roads and rivers. Thus, the expansion of urban areas and the development of the road network enhanced the connectivity and aggregation of rubber (Table 5), while also leading to negative impacts on biodiversity, especially insects, such as beetles, spiders and wild bees [56,57]. In 1991, the Regulations on Lancang River Basin Protection in Xishuangbanna was passed for the purpose of the protection and rational exploitation of Lancang River Basin.…”
Section: Threats Of Rubber Plantationsmentioning
confidence: 99%
“…This can be confirmed by species diversity, soil quality, and fine root biomass, etc. in the soil profile of PT, which are relatively lower than NF [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, our results clearly showed that the forest coverage was from 40% in SY to 80% in SC at the county scale, which was much higher than the mean value at the national level (21%), however, most of the forests were in remote and steep-sloped areas that were highly fragmented and uneven ( Table 4 and Figure 5 ). This results in a reduction in the actual ecosystem services of forests, in particular, water and soil conservation, biodiversity, and recreation [ 46 , 47 ]. Thus, there are two silvicultural measures to be stressed in forest management for this region.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, this affected the value of the ESs [47,49]. Landscape patterns changes could also be related to the alteration of hydrological cycles, microclimates in the watershed, and soil nutrients [50,51].…”
Section: Mechanisms Underlying the Impact Of Landscape Pattern Changes On Ecosystem Servicesmentioning
confidence: 99%